2023
DOI: 10.3390/ijms24043748
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products as Modulators of Nrf2 Signaling Pathway in Neuroprotection

Abstract: Neurodegenerative diseases (NDs) affect the West due to the increase in life expectancy. Nervous cells accumulate oxidative damage, which is one of the factors that triggers and accelerates neurodegeneration. However, cells have mechanisms that scavenge reactive oxygen species (ROS) and alleviate oxidative stress (OS). Many of these endogenous antioxidant systems are regulated at the gene expression level by the transcription factor Nrf2 (nuclear factor erythroid 2-related factor 2). In the presence of prooxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 141 publications
(154 reference statements)
0
19
0
Order By: Relevance
“…Thus, an increase in Nrf2 transcriptional activity is detected as an increase in cellular EGFP fluorescence in the transduced cells. Transduced cortical astrocytes treated with curcumin (10 μM), a known Nrf2 activator that serves as a positive control in the reporter assay 25,26,29,46 , showed a 5 to 8-fold increase in EGFP fluorescence intensity compared to control cells (data not shown). Cortical astrocytes treated with extract prepared from BB, wild BB, or GSk, or with the individual ANC C3G, D3G, or M3G, showed a ~1.3 to 2.0-fold increase in EGFP fluorescence relative to control levels (Figure 5).…”
Section: Effects Of Botanical Extracts On Nrf2 Transcriptional Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, an increase in Nrf2 transcriptional activity is detected as an increase in cellular EGFP fluorescence in the transduced cells. Transduced cortical astrocytes treated with curcumin (10 μM), a known Nrf2 activator that serves as a positive control in the reporter assay 25,26,29,46 , showed a 5 to 8-fold increase in EGFP fluorescence intensity compared to control cells (data not shown). Cortical astrocytes treated with extract prepared from BB, wild BB, or GSk, or with the individual ANC C3G, D3G, or M3G, showed a ~1.3 to 2.0-fold increase in EGFP fluorescence relative to control levels (Figure 5).…”
Section: Effects Of Botanical Extracts On Nrf2 Transcriptional Activitymentioning
confidence: 98%
“…Nrf2 is a redox-responsive transcription factor responsible for regulating the expression of cellular antioxidant proteins 44 . Multiple lines of evidence suggest that polyphenols modulate Nrf2 transcriptional activity 25,26,29,45,46 . Because PQ and rotenone are both thought to elicit neurotoxicity by eliciting oxidative stress, we hypothesized that at least a subset of botanical extracts might protect dopaminergic neurons against PD-related toxins by activating the Nrf2mediated antioxidant response.…”
Section: Effects Of Botanical Extracts On Nrf2 Transcriptional Activitymentioning
confidence: 99%
“…These cellular mechanisms collectively highlight terpenoids' potential as neuroprotective agents, offering avenues for therapeutic interventions in neurodegenerative disorders characterized by Aβ‐induced inflammation and oxidative stress. Terpenoids have been demonstrated to elicit the activation of the Nrf2 signalling pathway, leading to augmented synthesis of crucial antioxidant enzymes, notably HO‐1, NQO1, SOD, and CAT (Moratilla‐Rivera et al, 2023). This orchestrated response ultimately serves to curtail ROS production and mitigate neuronal damage (Branca et al, 2020).…”
Section: Intricate Interplaymentioning
confidence: 99%
“…In particular, this phenolic compound can be produced by Tetraselmis suecica and Nannochloropsis gaditana [ 174 ]. It was reported that quercetin can directly scavenge free radicals due to the presence of two antioxidant pharmacophores in the molecule, induce the expression of NRF2, and also inhibit ROS-associated inflammation by blocking IKK-β and the nuclear translocation of NF-kB [ 175 , 176 , 177 ] ( Figure 2 ). Quercetin can be integrated into the diet to stimulate insulin secretion, to protect beta cells from ROS, and to ameliorate the antioxidant defence and inflammation, therefore improving IR [ 178 ].…”
Section: Microalgal Molecules With Antioxidant Actionmentioning
confidence: 99%